Sex-based differences in outcomes among surgically treated patients with HPV-related oropharyngeal squamous cell carcinoma. (December 2021) - Shinn, Justin R.; Carey, Ryan M.; Mady, Leila J.; Shimunov, David; Parhar, Harman S.; Cannady, Steven B.; Rajasekaran, Karthik; Lukens, John N.; Lin, Alexander; Swisher-McClure, Samuel; Cohen, Roger B.; Bauml, Joshua M.; et al.
Highlights: Fewer women are affected by HPV-related oropharyngeal squamous cell carcinoma. It is unknown if there are sex-based differences in outcomes with surgical treatment. No differences were found between sexes in overall or recurrence-free survival. Women present with less disease than men and are more likely to undergo surgery alone. Abstract: Objectives: Sex differences in surgically treated HPV-associated oropharyngeal squamous cell carcinoma are not defined due to the low number of affected women. We explored the oncologic outcomes of men and women with p16-positive oropharyngeal squamous cell carinoma treated with primary surgery. Materials and Methods: Retrospective analysis of patients with HPV-related oropharyngeal cancer treated with surgery and pathology guided adjuvant therapy from 2007 to 2017. Primary end point was recurrence-free and overall survival. Results: Of 468 men (86.7%) and 72 women (13.3%), women presented more often with clinical N0 nodal disease (25% vs 12.2%). There were no differences in adverse pathologic features or T stage, although women were more likely to present with N0 disease (16.7% vs 10%), less N2 disease (6.9% vs 17.7%, p = 0.03), and more stage I disease (88.9% vs 75%). As a result, women were more likely to undergo surgery alone (30.6% vs 14.1%) while men were more likely to require adjuvant radiation therapy (47.2% vs 36.1%). Four women (5.6%) and 30 men (6.4%, p = 0.8) died during follow-up. Multivariate analysis controlling for age, sex, treatment, and pathologic stage demonstrated no differences in overall survival between men and women. There were no differences in recurrence-free or overall survival between men and women at two and five years. Conclusions: Although women undergoing transoral robotic surgery for HPV+ oropharyngeal squamous cell carcinoma may have less advanced disease, upfront surgery with pathology-guided adjuvant therapy produces similar oncologic results in men and women while accounting for disease burden.